History of Florence and of the affairs of Italy : - Machiavelli, Niccolo (Harper & Row, 1960)
Niccolo Machiavelli, the first great Italian historian, and one of the most eminent political writers of any age or country, was born at Florence, May 3, 1469. He was of an old though not wealthy Tuscan family, his father, who was a jurist, dying when Niccolo was sixteen years old. We know nothing of Machiavelli's youth and little about his studies. He does not seem to have received the usual humanistic education of his time, as he knew no Greek.